Public and private sector help scale Aflasafe and increase awareness and capacity to mitigate aflatoxin in Burkina Faso and Ghana - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In 2019, public and private sector actors launched initiatives to help scale Aflasafe and increase awareness and capacity to mitigate aflatoxin in Ghana and Burkina Faso. Collaborative partnerships like these help countries sensitise value chain actors and consumers to aflatoxins, while at the same time increasing demand for safer food and awareness of and demand for solutions. IITA works through partnerships to provide technical assistance in implementing strategies that raise awareness of the problem and solutions.